THE ROLE OF PANCASILA EDUCATION IN THE IMPLEMENTATION OF HUMAN RIGHTS TO PROTECT THE RIGHTS AND DIGNITY OF STUDENTS - Yaumil Khairiyah A.Cikdin; Nasiwan; Pardosi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The protection of students’ rights and dignity is a central issue in education because schools are not merely places for the transfer of knowledge, but also spaces where justice, equality, and respect for human dignity must be realized. This study employs a descriptive qualitative approach at a high school in Samarinda, Indonesia. Data were collected through observation, semi-structured interviews with the principal, Pancasila Education teachers, and three students, as well as documentation of instructional materials and school policies. Data were analyzed through data reduction, data presentation, and drawing conclusions. The findings indicate that Pancasila Education supports the implementation of human rights by strengthening students’ understanding of rights and responsibilities, fostering equality and justice in classroom interactions, promoting respect for human dignity, and encouraging anti-discriminatory attitudes. The uniqueness of this study lies in its practical analysis of how Pancasila Education operates as a human rights-based pedagogical instrument within the daily school culture, rather than merely as a normative or conceptual subject. Strengthening Pancasila Education through teacher role modeling, participatory learning, and consistent school policies can help prevent bullying, discrimination, and demeaning treatment, while creating a safer, more inclusive, and dignified learning environment